Preloaded injectors used in a clinical study: videographic assessment and laboratory analysis of injector nozzle damage - Khoramnia, Ramin; Yildirim, Timur Mert; Weindler, Jan N.; Naujokaitis, Tadas; Dzhambazova, Mariyana; Auffarth, Gerd U. (Journal of cataract and refractive surgery, 2021)
Purpose: To evaluate quality and duration of implantation of 2 preloaded intraocular lens (IOL) injectors and assess postimplantation damage.Setting: The David J. Apple Center for Vision Research, Department of Ophthalmology, University of Heidelberg, Heidelberg, Germany. Design: Prospective, randomized, comparative study with laboratory investigation. Methods: Implantation videos and postuse injectors from 60 paired eyes of 30 bilateral cataract patients were included. Patient eyes were randomly assigned for implantation with 2 different preloaded injectors: the AutonoMe with a Clareon IOL (Alcon Laboratories, Inc.) and the iSert with a Vivinex IOL (Hoya Corp.). Videos were reviewed for events during the implantation procedure, and the duration of each step of implantation. Injector nozzles were examined under light and scanning electron microscopy. Damage was graded and correlated with the IOL power. Three months postoperatively IOLs were assessed for material changes. Results: IOL delivery was without any critical events in 60 of the 60 eyes. The implantation took 56 seconds with the AutonoMe and 44 seconds with the iSert (P < .05). Most AutonoMe injectors (29; 97%) showed no damage or slight deformation. In most of the iSert injectors (25; 80%), short or extended cracks were present, and damage lengths correlated with the IOL power. All IOLs were free of material changes, including glistenings, 3 months postoperatively. Conclusions: Both preloaded IOL injectors allowed a safe and convenient IOL delivery. Implantation of the Clareon IOL took, on average, slightly longer than that of the Vivinex IOL, mostly due to a slower IOL unfolding. The AutonoMe showed less nozzle tip damage than that of the iSert.